As relações amorosas do adolescente com histórico de violência intrafamiliar. - Andrade, Thais Afonso (2018)
Episodes involving intrafamily violence have been widely publicized in the media, besides of being a frequent theme in academic circles. Intrafamily violence is understood to mean any act or omission that impairs the physical and psychological integrity and the full development of a family member. Experiencing violence in the family context results in several consequences for adolescents, among them, the early experience of violent dating. Violence in teen dating refers to physical, sexual, psychological (emotional/verbal), digital, harassment, and financial violence in a loving relationship. Such phenomenon is still considered a predictor of conjugal violence. In this context, the general objective of the present study was to understand how the adolescent with a history of intrafamily violence builds his/her relationships. This is a qualitative research of an exploratory nature. Four adolescents participated in this multiple case study: three girls and one boy, between 15 and 18 years old, who were or are victims of intrafamily violence, and that they are dating or had dated, regardless of the duration of the relationship. The present investigation was carried out in two cities of the metropolitan region of Recife / PE. The sampling technique used was the snowball and the instrument for data collection was a semi-structured interview. The interviews were recorded, transcribed and subsequently submitted to content thematic analysis. In the results, it was verified among teenagers participants indicative elements of the intergenerational transmission of violence. The family relationships found in this research fail to provide a healthy affective relationship because of the physical and psychological suffering to which its members were and in some cases still are exposed. Suffering psychological violence from parents and/or caregivers through humiliation and offense was observed as the most difficult events to which adolescents were exposed. However, as a positive point, a nonlinear and non-deterministic relation of the phenomenon was evidenced; two-way violence between participants was not identified. Given the complexity of the topic, it is fundamental to carry out research that deepens the understanding of the relationship between the experience of intrafamily violence and the presence of violence in the dating experience among adolescents.